2019
DOI: 10.12659/ajcr.914303
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lymphoblastic Leukemia with Malignant Hypercalcemia: A Case Report

Abstract: Patient: Female, 6 Final Diagnosis: Acute lymphoblastic leukemia Symptoms: Abdominal pain • bloody diarrhea • malaise • vomiting Medication: — Clinical Procedure: Chemotherapy Specialty: Oncology Objective: Unusual clinical course Background: Malignant hypercalcemia is a rare finding in the pediatric population, even more rare in hematological malignancies, such as leukemia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Further case reports and studies in children were later recorded, including a study conducted in the United Kingdom between 2003 and 2014 that showed that although hypercalcemia can occur in any type of cancer, it was more common in children with leukemia ( 8 ). Other studies have shown the association of malignant hypercalcemia with precursor phenotype B leukemia, associated with a leukocyte count of less than 20,000/mm 3 , and hypercalcemia at the time of diagnosis, as it presented itself in our case ( 6 ). Currently, it is suggested that the presence of hypercalcemia in children with leukemia does not affect their prognosis ( 9 ).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Further case reports and studies in children were later recorded, including a study conducted in the United Kingdom between 2003 and 2014 that showed that although hypercalcemia can occur in any type of cancer, it was more common in children with leukemia ( 8 ). Other studies have shown the association of malignant hypercalcemia with precursor phenotype B leukemia, associated with a leukocyte count of less than 20,000/mm 3 , and hypercalcemia at the time of diagnosis, as it presented itself in our case ( 6 ). Currently, it is suggested that the presence of hypercalcemia in children with leukemia does not affect their prognosis ( 9 ).…”
Section: Discussionsupporting
confidence: 62%
“…Hypercalcemia can be present in approximately 0.5%–1.5% of malignancies ( 5 ). In adults, it is mostly described in solid tumors ( 6 ) and in some rare situations associated with acute leukemia or chronic myeloid leukemia, mainly in the accelerated phases of the disease or blast phase ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood calcium decreased to normal range within 48 h with one dose of zoledronic acid (0.05 mg/kg) ( 6 ). Bota et al reported that a 6-year-old child with ALL combined with hypercalcemia developed hypocalcemia 2 days after receiving calcitonin (4 U/kg, q12 h) and zoledronic acid (2 mg) ( 12 ). Therefore, in order to avoid rebound hypocalcemia, it is recommended to initiate zoledronic acid (0.0125–0.05 mg/kg) and pamidronate disodium (0.25–2 mg/kg, maximum 60 mg) at a small dose, and the duration of therapy should be limited to avoid hypocalcemia, hand and foot convulsions, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The blood calcium decreased to normal range within 48 h with one dose of zoledronic acid (0.05 mg/kg) (6). Bota et al reported that a 6-year-old child with ALL combined with hypercalcemia developed hypocalcemia 2 days after receiving calcitonin (4 U/kg, q12 h) and zoledronic acid (2 mg) (12). Therefore, in order to avoid rebound hypocalcemia, it is recommended to initiate zoledronic acid (0.0125-0.05 mg/kg) and pamidronate disodium (0.25-2 mg/kg, maximum 60 mg) at a small dose, and the duration of therapy should be limited to avoid hypocalcemia, hand and foot convulsions, etc.…”
Section: Discussionmentioning
confidence: 99%